Triangle Detection with Color Information - (:unkn) unknown (IEEE, 2010)
We propose a new algorithm for detecting triangles of uniform color within natural images, subject to certain limitations which will be addressed in forthcoming publications. The main application area in our mind is autonomous vehicle control or driver assistance subsystems, where our algorithm can be employed to detect triangle-shaped fiducials or road signs. The algorithm can easily be extended to detect arbitrary polygons.